PECTORALIS THORACICUS MUSCLE PERFORMANCE OF HYBRID CHICKEN (F1) DERIVED FROM CROSSBREED BETWEEN BROILER AND PELUNG (Gallus gallus gallus) - Saragih, Hendry Tri Sakti; Roosdianto, Iwan; Daryono, Budi Setiadi (Jurnal Kedokteran Hewan, 2017)
This research purpose was to study the phenotype characters of body weight and pectoralis thoracicus muscle performance of hybrid chicken (F1) derived from crossbreed between parent stock broiler strain Cobb-500 and Pelung (Gallus gallus gallus). The chicks were divided into 3 groups and each group consists of 5 days-old chicks (DOC). Group 1 (T1) was used as control involving DOC derived from crossbreed between female and male of broiler Cobb-500 strain. Group 2 (T2) involving DOC derived from crossbreed between female and male Pelung, while Group 3 (T3) was DOC derived from crossbreed between female broiler strain Cobb-500 and male Pelung. The chicken was grown up to 49 days to evaluate the body weight, the pectoralis thoracicus weight, the pectoralis thoracicus area, and myofiber area. Data were statistically analyzed using one way Anova. The results showed that the average of body weight in T1; T2; and T3 were 2,17086.02; 506.220.02; and 1,23868.25 g, respectively (P0.05). The average of pectoralis thoracicus muscle weight in T1; T2; and T3 were 165.0411.97; 21.262.44; and 68.741.94 g, respectively (P0.05). The average of pectoralis thoracicus muscle area in T1; T2; and T3 were 97.09,7; 616,4; and 63,41,8 cm2 , respectively (P0,05). The average of pectoralis thoracicus myofiber area in T1; T2; and T3 were 14.721.04; 4.662.1; and 13.131.3 m2 , respectively (P0.05). It was concluded that crossbreed between broiler strain Cobb-500 and Pelung improved the body weight and pectoralis thoracicus muscle performance of hybrid chicken (F1).